Exploring Destination Attractiveness as a Future Senior-Friendly Destination: The Case of Langkawi Island - Wee, Hassnah; Zulkifli, Nabila; Zakaria, Muhammad Aniq Anas; Azhar, Nurul Atiqah; Yunus, Muhammad Fahmi; Zailani, Nurul Farah Izzah (Advances in Social Sciences Research Journal, 2022)
The goal of this research is to look into Langkawi's desirability as a potential senior-friendly destination in Malaysia through the eyes of a middle-aged tourist. The four attractiveness dimensions of a prospective senior-friendly location developed in the research framework are attractions, accessibility, amenities, and complementary services. Malaysians aged 40 to 54 make up the study's sample population. The descriptive analysis is used in the study to expand on the data and interpret it into findings. One hundred twenty-six respondents found that attractions are the most impactful feature of a senior-friendly destination. Various cultural and historical monuments, such as Makam Mahsuri and Padang Mat Sirat, influenced middle-aged travellers' preferences and choices. The result also highlights four attractive factors that players in the Langkawi tourism industry can employ to increase tourist satisfaction and obtain a competitive advantage over other tourism locations. Stakeholders should work to improve the destination's attractiveness to fulfil the needs of senior tourists and make it a future senior-friendly attraction by 2050. The study results provide an opportunity for theoretical expansion in the highlighted academic and practical implications.